2021
DOI: 10.1016/j.ijporl.2021.110701
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology manifestations of COVID-19 in pediatric patients

Abstract: Background The coronavirus disease 2019 pandemic has affected millions of people since its outbreak in December 2019. Limited data exist on otolaryngology manifestations of COVID-19 in pediatrics. This study aims to discuss the clinical features of COVID-19 in pediatrics, with an emphasis on otolaryngology manifestations. Methods The study included 660 COVID-19 laboratory-confirmed positive pediatric patients (aged 3–15 years) diagnosed at King Abdullah Specialist Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…A higher prevalence is noted in older children. 9 This may be attributed to an age-related biological difference, or may be secondary to the inability of the children to identify or communicate these symptoms effectively. Regarding the pooled incidence, these symptoms affected less than a tenth of infected children.…”
Section: Discussionmentioning
confidence: 99%
“…A higher prevalence is noted in older children. 9 This may be attributed to an age-related biological difference, or may be secondary to the inability of the children to identify or communicate these symptoms effectively. Regarding the pooled incidence, these symptoms affected less than a tenth of infected children.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the laboratory findings showed that among hospitalized patients, lymphocytopenia and leukopenia, in addition to elevated levels of ferritin, D-dimer, and C-reactive proteins, were encountered (Almoosa et al, 2020;Alnajjar et al, 2021;Mosalli et al, 2021;Shahin et al, 2021). The mortality rate was very low in the infected children of this country, with this latter not exceeding four deaths among all reports (Almoosa et al, 2020;Alnajjar et al, 2021;Alshengeti et al, 2021;Asseri et al, 2021;Hijazi et al, 2021;Kari et al, 2021b;Mosalli et al, 2021;AlGhamdi et al, 2022). Interestingly, in one study, it was found that 21% of hospitalized children infected with SARS-CoV-2 developed acute kidney injury.…”
Section: Childrenmentioning
confidence: 91%
“…In the Kingdom of Saudi Arabia, studies have shown a dominant benign prognosis of COVID-19 disease in children. A substantial portion were asymptomatic ( Ahmad et al, 2021 ; Almuzaini et al, 2021 ; Hijazi et al, 2021 ) with this rate ranging from 27.9% ( Mosalli et al, 2021 ) to 54.6% ( Alharbi et al, 2021 ). Among symptomatic ones, the most common reported symptoms were fever, cough, runny nose, and shortness of breath ( Harbi et al, 2020 ; Ahmad et al, 2021 ; Alharbi et al, 2021 ; Alshengeti et al, 2021 ; Mosalli et al, 2021 ; Shahin et al, 2021 ; AlGhamdi et al, 2022 ).…”
Section: Childrenmentioning
confidence: 99%
See 2 more Smart Citations